USULAN PENINGKATAN EFEKTIVITAS PADA MESIN BOILER PT. INDAH KIAT SERANG DENGAN KONSEP TOTAL PRODUCTIVE MAINTENANCE - Suharjo, Suharjo (Universitas Mercu Buana, 2014)
Abstract. PT. Indah Kiat Pulp & Paper Boiler Departement is apart of productiondepartement which produces steam that can not be separated from issues thatcorresponded with the Effectiveness of the machine caused by six big losses.Hence, some effeetive and effecient steps are needed to overcome and prevent theissue. The purpose of this research were to find out everall equipmenteffectiveness (OEE) value of the Boiler machines to analyze the six big lossesfactors, and to purpose improvement efforts based on total productivemaintenance (TPM) concept this research used OEE measurement method six biglosses, calculation analysis and cause effeect diagram to examine existingproblem to give solution improvement for the problem. The results shower thatthe average OEE value of three boiler machine is not meeting standards of basetarget companies. The most effecting factors of OEE value were reduced speedlosses and breakdowns losses. The proposed action for improve boiler machineeffectiveness were by utilizing autonomous maintenance according to TPMconcept.Keyword: Total productive Maintenance, Overall Equipment Effectiveness, sixbig losses.